Profile design and simulation verification of hard whirling tool for ZC1 worm machining. (June 2023) - Yu, Yaxin; Ji, Xiaoyan; Dai, Sheng; Zuo, Dunwen; Song, Shuquan
The profile of the hard whirling tool for ZC1 worm machining is challenging to design precisely. An inaccurate tool profile results in irreversible overcutting or additional machining allowance. This study aimed to develop an accurate tool profile design method and digital verification approach to enhance the quality of ZC1 worms. The precise measurement and axial section data acquisition of the worm are conducted. A tool profile design method is proposed based on the envelope of the equidistant axial section. The motion law of whirling is studied, and a 3D model generation procedure for worm teeth is developed. The effect of the tool profile design is verified, and the impact of cutting parameters on worm tooth profile error is analyzed. The results show that the presented tool design method can effectively avoid overcutting. The employed modeling approach of worm teeth provides an intuitive verification means for tool profile design. Variable cutting parameters lead to different machining errors, and the maximum error is less than 3 μm. Changing the cutting parameters will not induce macro profile error but will impact the micromorphology. These findings should be valuable for designing envelope machining tools with complex motion and realizing the superior performance of hard whirling for ZC1 worm machining.